STRATEGI PENANGANAN PEMBIAYAAN BERMASALAH PADA PRODUK PEMBIAYAAN MURABAHAH DI KOPERASI SIMPAN PINJAM KARYA USAHA MANDIRI BOGOR (KSPPS KUMS BOGOR) CABANG JONGGOL - Nanda Suganda; Rully Trihantana; Hasbi Ash Shiddieqy (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2021)
ABSTRACT Non-performing financing is financing where there are irregularities in returns that result in delays in payments so that judicial action is needed in return, there is even a possibility that the cooperative will be harmed. The data for NonPerforming Financing KSPPS KUM Bogor Jonggol Branch where in 2018 it was 4% and in 2019 it was 5%. This percentage cannot be said to be good because the NPF ratio is still at 5% in 2019. For that, a strategy is needed that can be used to reduce or even prevent the non-performing financing. So the author took the title